1989
DOI: 10.1111/j.1464-410x.1989.tb05213.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unilateral Vesicoureteric Reflux on Renal Growth and the Uptake of 99mTc DMSA by the Kidney. An Experimental Study in the Minipig

Abstract: The influence of unilateral vesicoureteric reflux (VUR) on renal growth and the uptake of 99mTc DMSA by the kidney has been investigated in a 2-kidney model in the growing minipig over a period of approximately 5 months. Animals with reflux in association with low voiding pressures and normal bladder function (n = 5), as well as those with raised voiding pressures and abnormal bladder function (n = 7), were investigated with appropriate non-refluxing controls (n = 12). Urinary infection and renal scarring were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…There was no significant difference in the kidney weights between the refluxing and non-refluxing sides in this study. These results concur with those of previous authors [18,19] using a pig model, and confirmed that sterile refluxing urine had no influence on renal growth.…”
Section: Discussionsupporting
confidence: 93%
“…There was no significant difference in the kidney weights between the refluxing and non-refluxing sides in this study. These results concur with those of previous authors [18,19] using a pig model, and confirmed that sterile refluxing urine had no influence on renal growth.…”
Section: Discussionsupporting
confidence: 93%
“…This was recently supported in an experimental study [7]. After operative or with conservative reflux therapy, determi nation of further renal growth can be used as an indica tion of success, one of the most accurate means of deter mining renal growth being the measurement of paren chymal area [8][9][10].…”
Section: Introductionmentioning
confidence: 86%